The Da Vinci code - Brown, Dan (New York : Doubleday, 2003)
Harvard symbologist Robert Langdon and French cryptologist Sophie Neveu work to solve the murder of an elderly curator of the Louvre, a case which leads to clues hidden in the works of Da Vinci and a centuries-old secret society.
Keywords: Art museum curators -- Crimes against -- Fiction; Detective and mystery fiction